2022
DOI: 10.1155/2022/7396816
|View full text |Cite|
|
Sign up to set email alerts
|

Architectural Interior Design and Space Layout Optimization Method Based on VR and 5G Technology

Abstract: With the continuous optimization of the living environment, people’s requirements for its comfort and cultural taste are also constantly improving, and their understanding and requirements for the appearance and style of the building and the layout of the building space have been further deepened, thus forming a situation of diversification and diversification of the style and form of the architectural appearance and interior design. There are a lot of layout problems in modern engineering and real life, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This section examines the existing methods like MDP (Ran & Dong, 2022), VR (Wu, 2022), and AI (Di & Yu, 2021) with time consumption, accuracy prediction, precision value, and the recall factor by comparing with our recommended strategy. Python 3.7 is used to implement the models for accurate selections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section examines the existing methods like MDP (Ran & Dong, 2022), VR (Wu, 2022), and AI (Di & Yu, 2021) with time consumption, accuracy prediction, precision value, and the recall factor by comparing with our recommended strategy. Python 3.7 is used to implement the models for accurate selections.…”
Section: Resultsmentioning
confidence: 99%
“…The scene redirection solution has successfully been tested, according to the findings. The study used a redirection algorithm's efficacy which is shown by comparison with the outcomes of uniform scaling(Wu, 2022). The study case simulated two reinforcement learning agents in a cooperative learning setting to discover the ideal 3D layout for the Markov decision process (MDP) formulation.…”
mentioning
confidence: 99%
“…For instance, the organization of indoor spaces within buildings plays a fundamental role in shaping IEQ. Research in this area emphasizes the significance of spatial layout, room arrangement and the efficient utilization of space (Wu, 2022). A well-organized indoor space not only enhances functionality but also influences factors such as ventilation and natural lighting.…”
Section: Review Of Building Designs In Relation To Indoor Environment...mentioning
confidence: 99%
“…Moreover, considerations such as privacy, acoustics and access to natural light influence the comfort and satisfaction of building occupants. Thus, designing spaces that offer adequate privacy, minimize noise disturbances and provide access to daylight contribute to a positive IEQ and foster occupant well-being (Wu, 2022). Supporting facilities and amenities within buildings, such as restrooms, break areas and recreational spaces, are also integral to enhancing IEQ (Ikuabe et al, 2021).…”
Section: Review Of Building Designs In Relation To Indoor Environment...mentioning
confidence: 99%
“…The pursuit of improved comfort in living environments has led to a diverse range of architectural styles and interior designs (Wu, 2022). Presently, optimizing interior spaces, including comfort, lighting, aesthetics, and layout, has become a significant research focus, necessitating a human-centric approach.…”
Section: Limits Contributionsmentioning
confidence: 99%